Caught basking in the winter sun: Preliminary data on winter thermoregulation in the Ethiopian hedgehog, Paraechinus aethiopicus, in Qatar. (February 2016) - Abu Baker, Mohammad A.; Reeve, Nigel; Mohedano, Ivan; Conkey, April A.T.; Macdonald, David W.; Yamaguchi, Nobuyuki
Abstract: Biologists focus on thermoregulation of desert mammals in terms of how they minimize heat gain, and put less effort on how they maximize heat gain during the cooler months. Heat gain may contribute to significant energy savings in desert mammals when the ambient temperature is substantially lower than body temperature. We investigated winter thermoregulation in free-ranging Ethiopian hedgehogs, Paraechinus aethiopicus, during winter using radio-telemetry in Qatar. Hedgehog temperatures ( Animal T a ) were significantly higher than ambient temperatures ( T a ) throughout the day, the difference was more extreme during the mid-day. We observed several hedgehogs basking with their radio-tags exposed to direct sunlight. We suggest that basking is beneficial for the hedgehog's thermoregulation in the desert where plenty of solar radiation is available with few predators. This is the first report of basking in the subfamily Erinaceinae. Highlights: We studied the winter thermoregulation in the Ethiopian hedgehog in Qatar using radio-telemetry. Hedgehog temperatures higher than ambient temperatures throughout the day, especially during the mid-day. We encountered several hedgehogs basking with their radio-tags exposed to direct sunlight. Basking is beneficial for the hedgehogs in the desert where plenty of solar radiation is available with few predators. Basking may contribute to energy savings in desert mammals when the Ta is substantially lower than Tb .